Measurement of the Lambda(0)(b) lifetime in the decay Lambda(0)(b)-> J/psi Lambda(0) with the D0 detector - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (American Physical Soc, 2005)
We present measurements of the Lambda(b)(0) lifetime in the exclusive decay channel Lambda(b)(0)-> J/psi Lambda(0), with J/psi ->mu(+)mu(-) and Lambda(0)-> p pi(-), the B-0 lifetime in the decay B-0-> J/psi K-S(0) with J/psi ->mu(+)mu(-) and K-S(0)->pi(+)pi(-), and the ratio of these lifetimes. The analysis is based on approximately 250 pb(-1) of data recorded with the D0 detector in p (p) over bar collisions at root s = 1.96 TeV. The Lambda(b)(0) lifetime is determined to be tau(Lambda(b)(0))=1.22(-0.18)(+0.22)(stat)+/- 0.04(syst) ps, the B-0 lifetime tau(B-0)=1.40(-) (+0.11)(0.10)(stat)+/- 0.03(syst) ps, and the ratio tau(Lambda(b)(0))/tau(B-0)=0.87(-) (+0.17)(0.14)(stat)+/- 0.03(syst). In contrast with previous measurements using semileptonic decays, this is the first determination of the Lambda(b)(0) lifetime based on a fully reconstructed decay channel.